Awareness of India's national health insurance scheme (PM-JAY): a cross-sectional study across six states - Diletta Parisi; Swati Srivastava; Divya Parmar; Christoph Strupat; Stephan Brenner; Caitlin Walsh; Rupak Neogi; Sharmishtha Basu; Susanne Ziegler; Nishant Jain; Manuela De Allegri (Health Policy Planning, 2023)
The paper assessed socio-demographic and economic determinants of beneficiaries' awareness of the Pradhan Mantri Jan Arogya Yojana (PM-JAY), the national health insurance scheme launched in India in 2018, and their awareness of their own eligibility.
Keywords: Capacity building; National tuberculosis elimination program; Digital health; Tuberculosis